Innovative ecosystems for green agriculture: a four-Helix + intermediary model for rural development - Qiqi Chen; Jun Li (Frontiers in Sustainable Food Systems)
IntroductionGreen agriculture innovation requires synergistic collaboration among government, academia, industry, farmers, and intermediaries to drive sustainable rural development.MethodsWe constructed a “Four-Helix + Intermediary” model and evaluated it using a harmonious development (HD) coefficient based on multi-omics field data from the soapberry industry in Queshan County.ResultsThe overall synergy coefficient among actors reached 0.6821 (“relative synergy”), with high coordination in government–enterprise investment and farmer satisfaction, but weaker university–enterprise collaboration and farmer labor input.ConclusionInstitutionalizing intermediary roles and targeted policy mechanisms can enhance collaborative innovation, offering a replicable framework for green agriculture and rural revitalization.